THE ROLES OF GLASS BLOCK APERTURES IN NATURAL LIGHT DISTRIBUTION FOR THE PRODUCTION ACTIVITY OF CV. EVERGREEN BUANA SANDANG - Priyadi (Jurnal Riset Arsitektur, 2017)
Abstract- A factory within the industrial field is both productive and commercial, with profit as its main orientation of activity. One of the efforts to minimize production cost in a factory is electricity saving through optimizing the utilization of natural lightning as a substitute for the use of lamplight. The lighting design in a factory area of production has to concur with specific activities conducted. The level of illumination and sufficient illumination comfort may improve both workers’ eyesight and concentration. Glass blocks form one of the commonly chosen materials to be applied as natural light apertures. From an economic point of view, glass block material has an edge in terms of low production cost and maintenance. CV. Evergreen Buana Prima Sandang, as children’s clothing factory utilizes natural lighting through glass block apertures, applied to the entire production area and all production stages from beginning to end. Based on theoretical study, they cannot be used to optimize natural lighting in a room, because there is no control over the direction and quality of incoming light. As a host of different activities, the factory’s production area requires a differing quantity of lighting. The research was conducted with the descriptive method and the quantitative approach, starting from initial observation of the study object, the medium of interviews and study of the relevant background literature derived from numerous sources. This was followed by direct measurement in the field as well as design simulation of natural lighting. In the analytical process, the influence of conditions around the spot on the intensity of the light source is described along with the role of glass-block apertures in fulfilling the requirement of light intensity illuminating work space, the influence of types and properties of glass blocks, as well as the influence of position and dimension of the apertures on natural light distribution covering each area of production. Keywords: glass block, natural light, production area, children’s clothing company